Laparoscopic Repair of a Chronic Iatrogenic Diaphragmatic Hernia - Blount, Andrew L. (Radiol Case Rep, 2015)
We report the diagnosis and repair of a chronic, iatrogenic diaphragmatic hernia using minimally-invasive techniques. A 69-year-old man presented with intermittent abdominal and shoulder pain. He had previously undergone laparoscopic Nissen fundoplication in which a grasper-induced puncture injury to the left hemidiaphragm was noted but not repaired. Radiographs and CT imaging diagnosed a left diaphragmatic hernia, with stomach herniated into the left thoracic cavity. This was repaired successfully via an intra-abdominal laparoscopic approach. This case represents the potential importance of repairing post-traumatic diaphragmatic hernia at the time that they occur, as well as a minimally invasive means for their repair.